Development of Articulate Storyline Interactive Learning Media in Learning The History of Labako Batik Using Addie ModelTo Increase Learning Effectiveness - Muhammad Reza Firmansyah; Bambang Soepeno; Rully Putri Nirmala Puji; Sugiyanto Sugiyanto; Guruh Prasetyo; Jefri Rieski Triyanto (JURNAL HISTORICA, 2021)
Education in the digital era prioritizes students' ability to capture information. The purpose of this research is to produce a validated product in the form of Articulate Storyline interactive learning media and to increase effectiveness in learning. The research development procedure was carried out using the ADDIE model development. The results of the validation of content experts in the field of study reached a percentage of 88% with very good qualifications, expert validation of learning media reached a percentage of 87% with very good qualifications, and language validation reached 88% with very good qualifications. In the small group trial, there was an increase in the average pre-test score from 50.00 to 81.11 and the field trial an increase in the average pre-test score from 45.81 to 81.44. The effectiveness measured by the relative effectiveness formula reached 62.2% with high effectiveness.